SREBP2 as a central player in cancer progression: potential for targeted therapeutics - Chen, Ruiqi; Chen, Tianyu; Li, Xiang; Yu, Junfeng; Lin, Min; Wen, Siqi; Zhang, Man; Chen, Jinchi; Yi, Bei; Zhong, Huage; Li, Zhao (Frontiers in Pharmacology, 2025)
Recent studies have identified the reprogramming of lipid metabolism as a critical hallmark of malignancy. Enhanced cholesterol uptake and increased cholesterol biosynthesis significantly contribute to the rapid growth of tumors, with cholesterol also playing essential roles in cellular signaling pathways. Targeting cholesterol metabolism has emerged as a promising therapeutic strategy in oncology. The sterol regulatory element-binding protein-2 (SREBP2) serves as a primary transcriptional regulator of genes involved in cholesterol biosynthesis and is crucial for maintaining cholesterol homeostasis. Numerous studies have reported the upregulation of SREBP2 across various cancers, facilitating tumor progression. This review aims to provide a comprehensive overview of the structure, biological functions, and regulatory mechanisms of SREBP2. Furthermore, we summarize that SREBP2 plays a crucial role in various cancers and tumor microenvironment primarily by regulating cholesterol, as well as through several non-cholesterol pathways. We also particularly emphasize therapeutic agents targeting SREBP2 that are currently under investigation. This review seeks to enhance our understanding of SREBP2’s involvement in cancer and provide theoretical references for cancer therapies that target SREBP2.